Theme-Based Instruction (TBI) Through Role-Play To Teach Students Of The Hospitality Program In Speaking Activities - Dr. Ririn Pusparini, M.Pd; Lucky Prihar Tanti (Journal of Innovative and Creativity, 2025)
This study examines how theme-based instruction (TBI) through role-play activities is implemented by teachers for students in the hospitality program at one of the vocational high schools in Surabaya. The study employed a qualitative method, conducted in two meetings. Data were collected using an observation checklist and a speaking scale. The first meeting focused on the implementation process of theme-based instruction through role-playing by the teacher. The second meeting focused on the students' performances after the implementation of theme-based instruction (TBI) through role-play in the classroom. The results showed that the implementation of theme-based instruction (TBI) through role-play significantly aided the teacher in teaching the students’ speaking skills, as it utilized real-life contexts related to the learning material. This approach also fostered students' interest in learning the English language, particularly in developing their speaking skills. This study contributes to the theoretical discourse on Theme-Based Instruction (TBI) and role-play activities, and recommends future research across disciplines and comparative tools for a deeper understanding of the implementation of Theme-Based Instruction (TBI) and role-play activities.